Pengabdian Masyarakat di Desa Trusmi Wetan Mengenai Menjaga Kebersihan dan Kesehatan Organ Reproduksi Wanita - Liliek Pratiwi; Seviani Hartanti; Laudya Revana Winarno; Dinda Rizki Andika; Cucu Cucu; Khusnul Rohima Labibah; Ike Nurlaeni; Sharla Servia Azzahwa; Lintang Istiqomah; Amelia Sri Rahmawati; Karin Karin; Fuzi Nur Fauziah; Sofi Riva Indriani; Shifa Salsabila; Nesah Nesah; Ayu Linatin; Ayat Revita; Zaskia Nurizki Aulia Sari; Pindi Jaya Sapurti; Alisha Amalia Ihshani; Suhaetin; Adi Adi; Risdiyanto Risdiyanto; Muhammad Rizky; Khofifah Indriyani; Essa Herlambang (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The reproductive organs are a highly sensitive area that requires careful hygiene and care, especially among adolescent girls who are susceptible to reproductive health issues such as vaginal discharge. One key preventative measure is consistent personal hygiene practices, particularly in maintaining vaginal hygiene. This practice is crucial to ensuring the area remains healthy, balanced, and free from infectious agents that can cause abnormal vaginal discharge or other health issues if left untreated or neglected. The primary objective of this community service initiative was to raise awareness and understanding of the importance of maintaining reproductive organ hygiene and health among adolescent girls. This activity was implemented and executed in two main phases. The first phase included an educational session delivered by fourth-semester nursing students, focusing on the importance of personal hygiene and reproductive health for adolescent girls. The second phase included an open discussion forum where participants were encouraged to ask questions, share experiences, and clarify their understanding of the material presented. The results showed a positive response from the participants. Most of them demonstrated increased awareness and understanding of reproductive hygiene and expressed their intention to consistently integrate proper care practices into their daily routines. This suggests that educational interventions, particularly those involving interactive communication, are effective in increasing knowledge and fostering health-conscious behaviors among adolescents. In conclusion, this program successfully contributed to improving participants' knowledge and attitudes in maintaining reproductive health, which is important for their overall well-being and long-term disease prevention efforts.